2016
DOI: 10.3171/2015.8.jns151390
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of infection after 754 cranioplasty operations and the value of intraoperative cultures for cryopreserved bone flaps

Abstract: Predictors of infection afterobJective The authors' aim was to report the largest study on predictors of infection after cranioplasty and to assess the predictive value of intraoperative bone flap cultures before cryopreservation. methods They retrospectively examined all cranioplasties performed between March 2004 and November 2014. Throughout this study period, the standard protocol during initial craniectomy was to obtain a culture swab of the extracted autologous bone flap (ABF)-prior to its placement in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…In review of literature bone ap infection rate after cranioplasty ranges from 5.9%-22%.in review of literature, Post-operative infection after CP method is stated to be 2-25.9% and SP method 2.3-18% (8,9,10,11,12).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In review of literature bone ap infection rate after cranioplasty ranges from 5.9%-22%.in review of literature, Post-operative infection after CP method is stated to be 2-25.9% and SP method 2.3-18% (8,9,10,11,12).…”
Section: Resultsmentioning
confidence: 98%
“…Post-cranioplasty bone ap infection is a clinical serious condition due to its consequences, including meningitis, brain abscess formation, encephalitis, system in ammation and sepsis. Thus, high index of suspicion and low diagnostic-threshold would be rational (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although, this method has many advantages but it is also followed by some major post operative complications and in some cases requiring the need of reoperation. In a study, one case was found where there was mild resorption of bone flaps although there was no infection or a need for reoperation for the complications during the follow-up periods.…”
Section: Review Of Evidencementioning
confidence: 99%
“…Although intraoperative spillage of the intestinal contents and intra-operative contamination from the environment clearly predispose to surgical site infections, intraoperative wound cultures have been shown not to be useful predictors of post-operative wound infections. (21,22) Wound infections that occur in the absence of intestinal content spillage, intestinal manipulation or intra-operative contamination are common. As an example, Methicillin resistant Staphylococcus aureus (MRSA) wound infections continue to occur even with strict adherence to pre-operative screening, intranasal decolonization and targeted parenteral antibiotic prophylaxis.…”
Section: Intestinal Microbiome and Surgical Site Infectionsmentioning
confidence: 99%